High Magnesium Calcite and Dolomite composition carbonate in Amphiroa (Lithophyllaceae, Corallinales, Rhodophyta): further documentation of elevated Mg in Corallinales with climate change implications. Issue 2 (26th December 2020) - Nash, Merinda C.; Adey, Walter; Harvey, Adela S.
Abstract : Species of the calcified, articulate coralline Amphiroa are key components of many shallow marine ecosystems. Understanding their mineral composition is important as their susceptibility to dissolution, due to ocean acidification, may vary with mineral composition. We studied the distribution of Mg‐calcite, very high magnesium calcite (VHMC), and dolomite within Amphiroa species to elucidate their mineral properties and susceptibility to dissolution. Results revealed that the asymmetrical X‐ray diffraction (XRD) pattern typical of Amphiroa globally represents high levels of VHMC and dolomite composition carbonate. The dolomite seems most likely to be disordered, but higher resolution XRD is required for confirmation. The calcified long sides of medullary cells have predominantly VHMC/dolomite and the corners have bands of VHMC/dolomite. Epithallial cell walls are low Mg‐calcite, and cortical cells are low Mg‐calcite with bands of VHMC. VHMC/dolomite is more stable than Mg‐calcite, and this may provide a competitive advantage for Amphiroa species as seawater pH declines. Further work is required to determine the metabolic controls on VHMC/dolomite mineral formation.